Real and Hyperbolic Matrices of Split Semi Quaternions - Alagoz, Yasemin; Ozyurt, Gozde (SPRINGER BASEL AG, 2019)
The aim of this paper is to investigate split semi quaternion matrices. To verify this, we first examine matrices with real split semi quaternion entries as a pair of hyperbolic matrices. Then, we present hyperbolic split semi quaternions and their matrices. Finally, for a hyperbolic split semi quaternion, we search some properties of its 2x2 matrix representation and we express 4x4 hyperbolic matrix and 8x8 real matrix representations.
Keywords: Split semi quaternion; Hyperbolic split semi quaternion; Split semi quaternion matrix; Hyperbolic split semi quaternion matrix; Mathematics; Physics